Divine attribution?: The interaction of religious and secular beliefs on climate change attitudes - Djupe, Paul A. (Politics and religion, 2023)
After five decades of research, there is still little consensus about the relation of religious variables to environmental attitudes. Even putting aside variations in sampling and measurement, we still have doubts about where modest consensus exists—the role of religious beliefs. Religious beliefs, such as mastery over nature, are more unstable than previously considered. Moreover, more importantly, these studies have generally failed to consider the role of secular beliefs about environmental problems and the interaction they may have with religion. Using data from a 2012 Public Religion Research Institute (PRRI) survey, we find religious variables have effects conditional on secular beliefs. Moreover, we draw upon an embedded experiment that shows instability in religious dominionism—the dominant religious effect in previous work. The results suggest previous reports of religious effects are not wrong, but overstated, and eliding secular beliefs is a serious sin of omission.